PENGARUH TARIF PAJAK PENGHASILAN, MEKANISME BONUS, DAN TUNNELING INCENTIVES TERHADAP PERGESERAN LABA DALAM MELAKUKAN TRANSFER PRICING DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Vinola Herawaty; Anne Anne (Jurnal Akuntansi Trisakti, 2017)
This study aims to examine the effect of income tax rates, bonus plan and tunneling incentives as instruments in detecting income shifting with transfer pricing with moderate good corporate governance. The independent variables in this research are income tax rate, bonus plan and tunneling incentives as well as leverage and firm size as control variables. Good corporate governance mechanism that has been used in this research is audit quality regarding to auditor reputation.The sample was taken by purposive sampling method consisting of 176 manufacturing companies of consumer goods industry sector listed in Indonesia Stock Exchange which have reported complete financial report in period 2013-2016. Test of hypothesis was using SPSS 23 application.The results show that good corporate governance has weaken positive significant for bonus plan and tunneling incentives in detecting income shifting in transfer pricing. Meanwhile, other independent variables income tax rate has no significant effect.